2016
DOI: 10.1298/ptr.e9896
|View full text |Cite
|
Sign up to set email alerts
|

Development of Overarm Throwing Technique Reflects Throwing Ability during Childhood

Abstract: ABSTRACT. Background : It is important to acquire fundamental movement skills during childhood. Throwing is a representative manipulative skill required for various intrinsic factors. However, the relationship between intrinsic factors and throwing ability in childhood is unclear. The purpose of this study was to investigate intrinsic factors related to the ball throwing distance of Japanese elementary school children. Methods: Japanese elementary school children from grades 1-6 (aged 6-12 years; n=112) partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
4
0
1
Order By: Relevance
“…Interestingly, most of the prior research on object control skills such as overarm throwing that examined associations between developmental sequences and outcomes has focused on changes in ball velocity rather than measures of ball accuracy, even though accuracy has as much or more ecological validity within a sports context (Luz, Rodrigues, De Meester, & Cordovil, 2017). In addition, much of the emphasis of this body of research rests on sequence identification (Gromeier, Koester, & Schack, 2017;Kasuyama, Mutou, & Sasamoto, 2016;Kobayashi et al, 2016); almost no theoretical or empirical attention rests on why particular body configurations exist or emerge. Perhaps surprisingly, researchers have also been mostly silent on factors that might prohibit or prevent individuals from transitioning from less developmentally advanced levels to subsequent, more proficient developmental levels, and over time, result in more successful outcomes (i.e., faster ball velocities, more accurate throws; Sternad, 2018).…”
Section: Understanding Changes In Developmental Sequencesmentioning
confidence: 99%
“…Interestingly, most of the prior research on object control skills such as overarm throwing that examined associations between developmental sequences and outcomes has focused on changes in ball velocity rather than measures of ball accuracy, even though accuracy has as much or more ecological validity within a sports context (Luz, Rodrigues, De Meester, & Cordovil, 2017). In addition, much of the emphasis of this body of research rests on sequence identification (Gromeier, Koester, & Schack, 2017;Kasuyama, Mutou, & Sasamoto, 2016;Kobayashi et al, 2016); almost no theoretical or empirical attention rests on why particular body configurations exist or emerge. Perhaps surprisingly, researchers have also been mostly silent on factors that might prohibit or prevent individuals from transitioning from less developmentally advanced levels to subsequent, more proficient developmental levels, and over time, result in more successful outcomes (i.e., faster ball velocities, more accurate throws; Sternad, 2018).…”
Section: Understanding Changes In Developmental Sequencesmentioning
confidence: 99%
“…Although there are few reports on throwing velocity in preschool children, similar results have be found on throwing velocity in this study because of the close relationship between throwing velocity and throwing distance. Kasuyama et al [5] reported that physical factors, such as body size, grip strength, endurance, and throwing motion, affect the throwing distance of young children. Demura [7] inferred that after the throwing movement matures to a certain level, physical fitness factors, such as power and coordination, contribute to the throwing distance.…”
Section: Discussionmentioning
confidence: 99%
“…The throwing ability of young children has been assessed by the throwing distance [1][2][3][4][5]. Many studies have reported that their throwing distance increases with age; moreover, the throwing ability is superior in boys as compared to girls [6,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…O arremesso, que é considerada uma das habilidades motoras manipulativas mais importante (1) , é inerente à infância durante o brincar (2) . A partir dos sete anos de idade, já é esperado que a criança apresente o padrão maduro deste movimento, porém a idade de aquisição destes padrões pode variar de acordo com a experiência das pessoas em diferentes ambientes (3) .…”
Section: Introductionunclassified